Kekuatan Hukum Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 32 Tahun 2017 Tentang Tata Cara Penyelesaian Sengketa Peraturan Perundang-Undangan Melalui Jalur Nonlitigasi - Amalia Hasnah; Abdul Qodir; Mufidah Mufidah (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThe Ministry of Law and Human Rights issued a legal product namely Ministerial Regulation Number 32 Year 2017 Concerning Procedure for Dispute Resolution of Legislation through Non-litigation. Whereas in the Ministerial Regulation gives new authority to the Ministry of Law and Human Rights to resolve conflicting laws and regulations disputes. This study uses a type of normative research that is by studying the literature, legislation, books, official documents, and writings of scholars relating to this research. In this study, the method of data collection is done by the study of literature. Data that has been collected and analyzed using descriptive-qualitative methods. The approach used in this research is the statutory approach and conceptual approach. The results of the study can be concluded that in the hierarchy of statutory regulations in Indonesia the status of the Ministerial Regulation is recognized as other regulations in Article 8 Paragraph (1) of Law Number 12 of 2011 concerning Formation of Laws and Regulations of the Minister of Law and Human Rights Number 32 of 2017 has a binding legal force because it is made by an authorized institution/official namely the Minister of Law and Human Rights. And with the issuance of these Regulations become a new alternative for the community to resolve conflicting norms and conflicting regulations outside the court more easily and quickly.Keywords: Legal Strength, Ministerial Regulation, Non-litigation.